Modalities of Moving to Inflation Targeting in Armenia and Georgia. (IMF Working Papers; Working Paper ;, 2007)
This paper reviews the current monetary and exchange rate policy frameworks in Armenia and Georgia, and the challenges associated with the choice of a credible nominal anchor in the context of large nominal and real shocks. The paper makes a case for a gradual transition to full-fledged inflation targeting (FFIT) in both countries in the medium term. The implications of this option are examined from various angles. In particular, the monetary transmission mechanisms and compliance with major institutional prerequisites for successful FFIT adoption are analyzed. Based on this analysis, the paper identifies a series of short- and medium-term recommendations, drawing on the experience of emerging market countries that successfully moved to FFIT.